Mutation of self-binding sites in the promoter of the MrpC transcriptional regulator leads to asynchronous Myxococcus xanthus development - McLaughlin, Maeve; Higgs, Penelope I. (Frontiers in Microbiology, 2023)
MrpC, a member of the CRP/Fnr transcription factor superfamily, is necessary to induce and control the multicellular developmental program of the bacterium, Myxococcus xanthus. During development, certain cells in the population first swarm into haystack-shaped aggregates and then differentiate into environmentally resistant spores to form mature fruiting bodies (a specialized biofilm). mrpC transcriptional regulation is controlled by negative autoregulation (NAR). Disruption of MrpC binding sites within the mrpC promoter region led to increased mrpC reporter expression and broadened distribution of mrpC expression levels between individual cells in the population, consistent with disruption of the MrpC NAR. Expression of mrpC from the mutant promoter led to a striking phenotype in which cells lose synchronized transition from aggregation to sporulation. Instead, some cells abruptly exit aggregation centers and remain locked in a cohesive swarming state, while the remaining cells transition to spores inside residual fruiting bodies. In situ examination of a fluorescent reporter for MrpC levels in developmental subpopulations demonstrated cells locked in the swarms likely contained intermediate MrpC levels. We hypothesize intermediate levels of MrpC are sufficient to promote aggregation but insufficient to trigger sporulation. These results suggest that in the M. xanthus multicellular developmental program, MrpC NAR can facilitate synchronized transitions of cell populations between developmental states.